Mulheres lésbicas e dificuldades de acesso à saúde: impactos na saúde mental - Oliveira, Gyselly Pereira de (Universidade Federal do Tocantins, 2024)
This research aims to understand how the mental health of lesbian women is impacted by the lack of information about sexual and reproductive health and the quality of health services provided and whether prejudice and discrimination interfere with the quality of sexual and reproductive health care of these women. The methodological path we adopted was an exploratory, descriptive and qualitative bibliographic review. To this end, we sought the production of scientific articles, in Portuguese, on the health of lesbian women indexed on digital platforms, in the period between 2006 and 2023, since the production is concentrated in this temporality, considering that 2006 was the year of publication of the Lesbian Women's Health Dossier - Promotion of Equity and Integrality, published by the Feminist Health Network. Our analysis was based on the guidelines of the Ministry of Health and on authors who approach the subject under study from a feminist perspective. From the development of our research, we found that studies on the subject of lesbian women total a very insignificant number, if compared to studies on male homosexuality, which indicates a double prejudice. In addition to the invisibility in scientific research, we also identified it with regard to public policies and technologies to prevent STIs/AIDS directed at this social segment. We verified that the mental health of lesbian women is negatively affected by the lack of information about sexual and reproductive health and reception and sexual orientation that deviates from the established norm, especially if analyzed from the perspective of social determinants of health. Contrary to what the health policy guidelines predict, health services are the protagonists of episodes of discrimination, invisibilities and institutional violence, despite this phenomenon occurring in the most diverse spaces of interaction in the daily lives of these women: such as at work and other social circles that coexist. The fear of talking about their sexuality within the services and the psychological/emotional violence due to their sexual orientation were also identified as determinants for a lack of access to health services, preventive information, reception and care. Finally, we emphasize that the uniqueness of the lesbian woman needs to be respected and health care must be inclusive, integral and humanized.